The Effect of Omega-3 Solution in the Prevention of Epidural Fibrosis Formation in Experimental Rabbit Hemilaminotomy Model - Çokluk, C.; Aydin, K.; Tümkaya, L. (My University, 2010)
The aim of this experimental study was to evaluate the effect of omega-3 fatty acids solution in the prevention of the forming of peridural fibrotic tissue and adhesion in a rabbit hemilaminotomy model. This new experimental model was previously developed by the first author of this study. Twenty-one New Zealand white rabbits were used for this experiment. Seven of them were randomly selected as Control group and was named as Group I rabbits. The rabbits in this group were not operated and treated. The second group was Group II including 7 rabbits. This group was named as hemilaminotomy and untreated rabbits. Group III included 7 rabbits and named as Omega-3 treated group after hemilaminotomy procedure. In this group (Group III), 250 mg omega-3 solution was put in the hemilaminotomy area before closing the skin and fascia. Four weeks later from the operation rabbits were sacrificied by perfusion with 10% neutral buffered formalin solution. The lumbar spines were removed and immersed in 10% neutral buffered formalin for approximately 24 hours. Then each specimen was decalcified in 5% formic acid for approximately 3 weeks. Specimens were cut coronally for gross inspection. Peridural scar tissue on gross inspection in coronal sectioned specimens was graded into three grades. Grade I epidural scar tissue was scored with 1 point, Grade II with 2 point and Grade III with 3 point. The average score of hemilaminotomy sites without treatment was found as 2, 6 ± 0, 51. In the other hand the average score of hemilaminotomy sites with omega-3 fatty acids treatment was found as 1, 9 ± 0, 56. The difference between the treatment and non-treatment group was statistically significant. Omega-3 fatty acids solution seems an effective treatment modality in the prevention of peridural excessive scar tissue formation in the rabbit hemilaminotomy model. © 2010 OMU All rights reserved.
Keywords: Fatty Acids; Hemilaminotomy; Lumbar Spine; Omega-3; Peridural Fibrosis; Rabbit